FUNGSI-FUNGSI PEMASARAN JAGUNG MANIS DI DESA RIDAN PERMAI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Astuti, Tia Widiya; Maharani, Evy '; ', Yusmini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Marketing is a social and managerial process where somebody groups obtain whatthey need and try through the creation, exchange to meet the needs, desires anddemands of a person or group. One mainstay of agricultural commodities are corn,because corn is a staple food in Indonesia, which has a fairly important position after rice. The research objective was to determine marketing functions performedby marketing institutions sweet corn in the village of Ridan Permai. The researchmethod used is survey method with a sample study of 25 people sweet cornfarmer, 2 collectors and 9 retailers. Marketing functions carried out by the farmers include the functions of buying, selling, transporting, storage, financing,underwriting risk and market information functions. Retailers perform the function of purchases, sales, transportation, storage, finance, underwriting risk and marketinformation functions. Farmers and traders do not carry out functions and Grading Standards for sweet corn is sold in the market tend not to have a clear standardization and grading, this is because there is no competent body to standardize or grading of the sweet corn sold. Standardization and grading functions usually only applies when the product is sweet corn for sale at a supermarket or mall.Keywords: Marketing Functions, Channel, Margins